STRATEGI UNTUK MENINGKATKAN KUALITAS OBAT BIOLOGI PADA SEL MAMALIA CHINESE HAMSTER OVARY (CHO) : SUATU KAJIAN PUSTAKA - Himawan, Alayna Lillahida Indri; Santoso, Adi; Septisetyani, Endah Puji; Prasetyaningrum, Pekik Wiji; Rahma, Nurul Maulida; Narayani, Inna (SIMBIOSIS; Vol 11 No 2 (2023)DO - 10.24843/JSIMBIOSIS.2023.v11.i02.p11, 2023)
Chinese hamster ovary (CHO) cells are essential cells frequently used to produce biopharmaceutical molecules, especially glycoproteins. Nevertheless, to obtain an efficient production process and effective therapeutic consistency, the right strategy is needed to improve the quality of biological drug products. It is known that all the critical molecules involved in the immune response are glycoproteins, and many therapeutic proteins, such as vaccines, antibodies, and enzymes, require glycans to have total biologic activity. This review discusses the strategy used in CHO cells to modulate sialylation patterns through overexpression of sialyltransferases, CMP-sialic acid transporter, UDP-GlcNAc 2-epimerase (GNE), ManNAc kinase (MNK), and other related enzymes. In addition to modulating biosynthetic pathways to increase sialic acid content with gene overexpression techniques, this review includes methods for inserting glycosylation sites and manipulating glycans to produce the desired glycoforms. An approach through protein fusion techniques with Fc molecules from human IgG is also discussed to increase the protein half-life. Finally, as a strategy to improve the quality of biopharmaceutical molecules, this review also discusses the importance of cell monoclonalization in developing a cell line that truly originates from a single clone. This is a very critical step to obtain batch to batch consistency during the production process of a biopharmaceutical molecule.